Additive antitumour response to the rabbit VX2 hepatoma by combined radio frequency ablation and toll like receptor 9 stimulation - Behm, Barbara; Di Fazio, Pietro; Michl, Patrick; Neureiter, Daniel; Kemmerling, Ralf; Hahn, Eckhart Georg; Strobel, Deike; Gress, Thomas; Schuppan, Detlef; Wissniowski, Thaddaeus Till (Gut, 2016)
Radiofrequency ablation (RFA), a palliative therapeutic option for solid hepatic tumours, stimulates localised and systemic antitumour cytotoxic T cells. We studied how far addition of CpG B oligonucleotides, toll like receptor (TLR) 9 agonists, would increase the antitumoural T cell response of RFA in the highly aggressive VX2 hepatoma.Rabbits were randomised to receive RFA, CpG B, their combination or no therapy. The antitumour efficacy of RFA alone or in combination with CpG B was further tested by rechallenging a separate group with intravenously injected VX2 tumour cells after 120 days. Animals were assessed for survival, tumour size and spread, and tumour and immune related histological markers after 120 days. Peripheral blood mononuclear cells were tested for tumour-specific T cell activation and cytotoxicity. Immune modulatory cytokines tumour necrosis factor ?, interleukin (IL)-2/IL-8/IL-10/IL-12 and interferon ?, and vascular endothelial growth factor were measured in serum.Mean survival of untreated animals was 36 days, as compared with 97, 78 and 114 days for RFA, CpG and combination therapy, respectively. Compared with untreated controls, antitumour T cell stimulation/cytotoxicity increased 26/16-fold, 32/17-fold and 50/38-fold 2 weeks after RFA, CpG and combination treatments, respectively. The combination inhibited tumour spread to lungs and peritoneum significantly and prohibited new tumour growth in animals receiving a secondary systemic tumour cell injection. RFA alone induced a Th1 cytokine pattern, while IL-8 and IL-10 were only upregulated in CpG treated animals and controls.The combination of TLR9 stimulation with RFA resulted in a potentiated antitumour T cell response and cytotoxicity in the VX2 tumour model. Only this combination prevented subsequent tumour spread and resulted in a significantly improved survival, justifying the need for further exploration of the combination of ablative therapies and TLR9 agonists in liver cancer.
EVALuna2:2070